EFEKTIVITAS TAYANGAN â€œYUK KEEP SMILEâ€ DI TRANS TV TERHADAP PEMENUHAN HIBURAN PEMIRSA DI KELURAHAN WALIAN - Rory, Stevani (ACTA DIURNA KOMUNIKASI, 2014)
EFFECTIVENESS DISPLAY " YUK KEEP SMILE" IN TRANS TV TO ACCOMPLISHMENT OF ENTERTAINMENT AMUSEMENT BEHOLDER IN SUB-DISTRICT OF WALIAN. Progress of technology this time fast so him expand, one of the communications technology is television. Television is one of the effective communication means in submitting information to society. This matter because television can present concurrently between voice and picture. With progress of television technology, we earn to witness direct broadcast a[n us although activity reside in far. This our seakan-akan witness to near from the activity. Television have excess to present broadcast directly (broadcasting live) tired which can. Pursuant to breakdown of research background above, hence which is formula in this research is : How Effectiveness Display " Yuk Keep Smile" In Trans TV To Accomplishment Of Entertainment Amusement Beholder In Sub-District of Walian.